Bibliography of Government Accounting Research In Indonesia: Bibliografi Penelitian Akuntansi Pemerintahan di Indonesia - Rusdi, Dedi; Suprianto, Edy (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to describe the development of government accounting research in Indonesia from 9 accredited journals in Indonesia indexed by sinta 2. The sample obtained from 2011 to 2021 obtained 45 articles discussing government accounting. Based on the results of the analysis, the majority of research on government accounting in Indonesia is published in JAAI and JAB respectively by 20%, while MRAAI is 11% and JAMAL is 16%. Of the 45 articles obtained, 11 articles are qualitative method research, while 34 articles are research using quantitative methods. In qualitative research the method of descriptive analysis or case studies is the most widely used, while in quantitative research the most widely used method is regression analysis